Innovative production machines and systems : Third I*PROMS Virtual Conference, 2nd-13th July 2007 - Pham, D. T.; Eldukhri, E. E.; Soroka, A. J. (Whittles ; Distributed in North America by CRC Press, 2008)
IPROMS 2007 is the third online, web-based conference on Innovative Production Machines and Systems organised by the EU-funded I*PROMS Network of Excellence. It continues to build on the two previous outstandingly successful conferences and attracted authors from 30 countries across 5 continents. There were 3600 registered delegates and guests from almost 70 countries participated, making it a truly global phenomenon. This volume of over 100 papers provides an invaluable state of the technology review and assessment, enabling readers to appreciate developments and potential in a number of exciting fields. It is a focal point for access to information from researchers and industrial practitioners in the field of intelligent systems and soft computing techniques and their application in diverse areas within manufacturing.